Job's Body and the Dramatised Comedy of Moralising: Job’s Body and the Dramatized Comedy of “Advice” - Southwood, Katherine (Routledge Studies in the Biblical World, 2021)
"This book focuses on the expressions used to describe Job’s body in pain and on the reactions of his friends to explore the moral and social world reflected in the language and the values that their speeches betray. A key contribution of this monograph is to highlight how the perspective of illness as retribution is powerfully refuted in Job’s speeches and, in particular, to show how this is achieved through comedy. Comedy in Job is a powerful weapon used to expose and ridicule the idea of retribution. Rejecting the approach of retrospective diagnosis, this monograph carefully analyses the expression of pain in Job focusing specifically on somatic language used in the deity attack metaphors, in the deity surveillance metaphors and in the language connected to the body and social status. These metaphors are analysed in a comparative way using research from medical anthropology and sociology which focuses on illness narratives and expressions of pain. Job's Body and the Dramatised Comedy of Moralising will be of interest to anyone working on the Book of Job, as well as those with an interest in suffering and pain in the Hebrew Bible more broadly."